A Review of Studies on Green Banking, Research Gaps and Future Directions - Nanda, Nabila; Suteja, Jaja; Gunardi, Ardi; Rusliati, Ellen; Sarman, Rohmat (Jurnal Perilaku dan Strategi Bisnis, 2023)
This study was conducted based on the phenomenon of climate change which became the focus of the banking world to adopt green banking practices. The objective of this study was to examine the influencing factors for the green banking disclosure from 20 private banks listed on the Indonesia Stock Exchange. The independent variables in this study were the size of the board of commissioners, institutional ownership, firm value and profitability. The relationship between the influencing factors and green banking disclosure was assessed by statistical descriptive analysis methods and multiple linear analysis. The results of this study are expected to contribute to academia, banking and government.